A határ menti szerep újraértelmezése Trianon után - Baranyi, Béla (Közép-Európai Közlemények, 2014)
The radical geopolitical restructuring after the First World War resulted in new states and state borders in Central Europe. As a result of the bargaining of great powers, the newly developed national states became the main barrier to the extension of interregional relations in Central Europe and mainly in Hungary. The hostile relations and mistrust coming from the new situation was not favourable for the relationship of Hungary with its neighbours. In addition to the new borders set by the Treaty of Trianon (1920) which drastically re-shaped the map of the Carpathian basin, as well as the unprecedented loss of territory and population, socio-economically, infrastucturally and ethnically organic spatial structural units and real regions were cut into pieces. For this reason, Hungaryneeded to reposition its cross-border relationship system in the decades to come. However, the most severe consequence which is a barrier to cross-border cooperation to this day is the “fragmentation” of the previously relatively uniform spatial structure, that is the development of external (cross-border) peripheries on both sides of the state borders. The elimination of the periphery character, the reduction of the separator role of borders, the re-establishment of the old economic-spatial structural and settlement relations, the strengthening of the cohesion of border regions, especially Hungary’s relations with its good neighbours, more specifically the improvement of Hungarian-Hungarian and interethnic relations have been important national political interests in the cooperation of the neigh-bouring countries. The realisation of the listed endeavours could be served by the currently ongoing paradigm shift which occurs as a result of the unfolding European integration and Schengen process, more specifically, the re-interpretation of cross-border roles and the drafting of future alternatives in the relation of the connecting border regions. In the new situation resulting as a positive consequence of the Schengen process, the study focuses on the possible content and form of the rebuilding of interregional relations in the internal border of the Schengen area since it is less restricted by country borders.